Iron-based radiochromic systems for UV dosimetry applications. (9th January 2018) - Lee, Hannah J; Alqathami, Mamdooh; Blencowe, Anton; Ibbott, Geoffrey
Abstract: Phototherapy treatment using ultraviolet (UV) A and B light sources has long existed as a treatment option for various skin conditions. Quality control for phototherapy treatment recommended by the British Association of Dermatologists and British Photodermatology Group generally focused on instrumentation-based dosimetry measurements. The purpose of this study was to present an alternative, easily prepared dosimeter system for the measurement of UV dose and as a simple quality assurance technique for phototherapy treatments. Five different UVA-sensitive radiochromic dosimeter formulations were investigated and responded with a measurable and visible optical change both in solution and in gel form. Iron(III) reduction reaction formulations were found to be more sensitive to UVA compared to iron(II) oxidation formulations. One iron(III) reduction formulation was found to be especially promising due to its sensitivity to UVA dose, ease of production, and linear response up to a saturation point.